Eksperimen Pembelajaran Matematika dengan Strategi Discovery Learning dan Problem Based Learning terhadap Hasil Belajar Matematika ditinjau dari Tingkat Motivasi Siswa Kelas VIII SMP Negeri 2 Sawit Tahun Ajaran 2016/2017 - Kusuma, Amelia Dyah Ayu; , Prof. Dr. Sutama, M.Pd (2017)
On this research has three purposes. (1) Examine the effect mathematics learning outcomes toward implementation Discovery Learning (DL) and Problem Based Learning (PBL), (2) Examine the effect mathematics learning outcomes toward the student's motivation level, (3) Examine interaction between learning strategies and student's motivation level toward mathematics learning outcomes. This research is quantitative quasi. The population in this research is all students of VIII SMP N 2 Sawit on academic year 2016/2017. Sample consisted of two classes, experiment class treated DL and control class treated PBL. Technique use Cluster Random Sampling. Methods of data collection used documentation and test. Techniques of analyzed used analysis of variance two path different cell. Before the test analysis is start, the sample must be tested prerequisites test normality and homogeneity test. The result of this research can conclude that: (1) there is a effect between discovery learning ang problem based learning toward mathematics learning outcomes student in SMP N 2 Sawit with significance 5%, (2) there is a effect between student's motivation level with mathematics learning outcomes student in SMP N 2 Sawit with significance 5%, (3) there is no interaction between learning strategies and student's motivation level toward mathematics learning outcomes with significance 5%. Keywords: discovery learning, motivation level, problem based learning